Evaluation of the Functionality of the Vida View Makassar Apartment Building in terms of Occupant Satisfaction - Karina Dwi Anggreni; Mimi Arifin; Idawarni J. Asmal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In urban areas, apartments are one of the residential solutions for residents given that the availability of land in urban areas is minimal. Vida View Apartment is one of the apartments in Makassar City. This study seeks to analyze the function-worthy aspects of buildings that have pocketed the Function-worthy Certificate issued by the Makassar City Spatial Planning Service in 2018, namely the Vida View Apartment. By conducting this research, it is expected to be able to find out the characteristics of the occupants and the level of satisfaction of the residents based on the technical study of livability at the Vida View Makassar Apartment. The data used came from 252 respondents who lived in the Vida View Apartment. The method used is observation, questionnaires, interviews, and documentation. The analysis was carried out with descriptive quantitative and descriptive qualitative and IPA (Importance-Performance Analysis) analysis. The results showed that 1) The characteristics of the residents of the apartment were 58% male, 60% residents aged around 15-30 years, and 78% of residents were natives of Makassar City. In addition, 61% of the dwellings are private residences, and 50% of the residents have occupied them for 1-3 years. 2) Based on the results of the IPA analysis, it is known that the occupancy comfort variable is divided into two categories, namely maintaining achievement and low priority so that there is a need for maximum improvement. The convenience variable in general has been implemented in accordance with expectations and the implementation of appropriate performance, but there are indicators of low priority. The safety variable shows that it needs to be handled and becomes a top priority to increase safety from pollution for apartment residents. In health variables, some indicators have met expectations, but there is one indicator that becomes a top priority, namely air conditioning, so handling is needed, while the orientation indicator to the sun is included in the low priority category.